Peningkatan Hasil Belajar Peserta Didik Dengan Model Pembelajaran Advance Organizer Dalam Pokok Bahasan Materi Anak SMA Boleh Pacaran Pada Mata Pelajaran Pendidikan Agama Kristen - Sertiana Siahaan (CV Putra Publisher, 2023)
This research is Classroom Action Research (CAR) conducted at SMA Negeri 5 Pematangsiantar which is located at Jalan. Medan Km. 6,8, Ex. Tanjung Tongah, Kec. Siantar Martoba, Pematangsiantar. The subjects of this study were students of class X PMIA 1 with a total of 15 students. The objectives of this study were 1) to find out whether there was a significant influence with the Advance Organizer learning model 2) to improve the cognitive abilities of students on the subject of high school children can date. The data collection techniques used are tests and observations. There are four stages of the procedure in this study, namely planning, implementing, observing, and reflecting. This research was conducted in two cycles where each cycle was carried out in two meetings. The results showed that learning completeness in cycle I was 46.67% increasing to 80% with an average score of 72 increasing to 90.67.